Atlantic Salmon (Salmo salar) Cage-Site Distribution, Behavior, and Physiology During a Newfoundland Heat Wave - Gamperl, Anthony K.; Zrini, Zoe A.; Sandrelli, Rebeccah M. (Frontiers in Physiology, 2021)
Abstract Background: Climate change is leading to increased water temperatures and reduced oxygen levels at sea-cage sites, and this is a challenge that the Atlantic salmon aquaculture industry must adapt to if it is to grow sustainably. However, to do this, the industry must better understand how sea-cage conditions influence the physiology and behaviour of the fish. Method: We fitted ~ 2.5 kg Atlantic salmon on the south coast of Newfoundland with Star-Oddi milli-HRT ACT and Milli-TD data loggers (data storage tags, DSTs) in the summer of 2019 that allowed us to simultaneously record the fish’s 3-D acceleration (i.e., activity / behaviour), electrocardiograms (and thus, heart rate and heart rate variability), depth and temperature from early July to mid October. Results: Over the course of the summer/fall, surface water temperatures went from ~10-12oC to 18-19.5oC, and then fell to 8oC. The data provide valuable information on how cage-site conditions affected the salmon and their determining factors. For example, although the fish typically selected a temperature of 14-18oC when available (i.e., this is their preferred temperature in culture), and thus were found deeper in the cage as surface water temperatures peaked, they continued to use the full range of depths available during the warmest part of the summer. Depth occupied by the fish and heart rate were greater during the day, but the latter effect was not temperature-related. Finally, while the fish generally swam at 0.4-1.0 body lengths per second (25 to 60 cm s-1), their activity and the proportion of time spent using non-steady swimming (i.e., burst-and-coast swimming) increased when feeding was stopped at high temperatures. Conclusion: DSTs that record multiple parameters are an effective tool to understand how cage-site conditions and management influence salmon (fish) behaviour, physiology and welfare in culture, and can even be used to provide fine-scale mapping of environmental conditions. The data collected here, and that in recent publications, strongly suggest that pathogen (biotic) challenges in combination with high temperatures, not high temperatures + moderate hypoxia (~ 70% air saturation) by themselves, are the biggest climate-related challenge facing the salmon aquaculture industry outside of Tasmania.